How to restore sustainability of the Euro? - Kari E. O. Alho (The Research Institute of the Finnish Economy (ETLA), 2011)
We reassess the result of unsustainability of the euro with respect to inflation differentials claimed by Wickens (2007) by specifying an open-economy version of a two-region New Keynesian model for EMU and demonstrate that the result by Wickens does not hold in general. We are able to derive a result that the model is determinate for a wide range of policy rules so that the sustainability of the euro area and the member countries is reached over time with respect to supply and demand shocks and emerged imbalances in price levels and competitiveness. We then enlarge the numerical analysis to consider EMU and sustainability in the case, prevailing currently, where a high debt country should both restore its competitiveness and its fiscal balance, and the policies required from the single monetary policy and the national fiscal policies. Strong fiscal consolidation and far-reaching successful structural reforms are needed to reach sustainability in the sense that emerged imbalances in competitiveness and price levels and the threat of ever mounting debt levels could be eliminated over the medium run. We also illustrate how the current deflationary adjustment involves a major polarisation in economic developments within the euro area.
Keywords: E43; E52; E62; 330; EMU; euro; sustainability; fiscal policy; competitiveness; Finanzpolitik; Internationaler Wettbewerb; Haushaltskonsolidierung; New-Keynesian Phillips Curve; Eurozone; EU-Staaten